Evolving an efficient and effective off-the-shelf computing infrastructure for schools in rural areas of South Africa - Siebörger, Ingrid Gisélle (Rhodes University, Faculty of Science, Department of Computer Science, 2017)
Upliftment of rural areas and poverty alleviation are priorities for development in South Africa. Information and knowledge are key strategic resources for social and economic development and ICTs act as tools to support them, enabling innovative and more cost effective approaches. In order for ICT interventions to be possible, infrastructure has to be deployed. For the deployment to be effective and sustainable, the local community needs to be involved in shaping and supporting it. This study describes the technical work done in the Siyakhula Living Lab (SLL), a long-term ICT4D experiment in the Mbashe Municipality, with a focus on the deployment of ICT infrastructure in schools, for teaching and learning but also for use by the communities surrounding the schools. As a result of this work, computing infrastructure was deployed, in various phases, in 17 schools in the area and a "broadband island" connecting them was created. The dissertation reports on the initial deployment phases, discussing theoretical underpinnings and policies for using technology in education as well various computing and networking technologies and associated policies available and appropriate for use in rural South African schools. This information forms the backdrop of a survey conducted with teachers from six schools in the SLL, together with experimental work towards the provision of an evolved, efficient and effective off-the-shelf computing infrastructure in selected schools, in order to attempt to address the shortcomings of the computing infrastructure deployed initially in the SLL. The result of the study is the proposal of an evolved computing infrastructure model for use in rural South African schools.
Keywords: Uncatalogued